The Obscene Thinking Voice - Cabide, Rodrigo (Opiniães, 2021)
This study analyses A obscena senhora D (1982), by Hilda Hilst, taking the “thinking literature” as a categorization made by Evando Nascimento (2015).  This theoretical proposition, for the researcher, outlines the particularity of literary writing by engendering meanings and perceptions of thinking apart from philosophy. Therefore, “obscene” effects and senses are analyzed in a comparative manner to the thinking exercises triggered by Hillé, the protagonist´s voice. As an unfolding of the proposition, there is a searching by the configuration of the “thinking” adjective through the orchestration of voices that alternate and combine gossiping and ruminance. Lastly, are considered the editorial resources and autobiographical backstage supported by the narrative thinking process.